2005
DOI: 10.1109/lsp.2005.859528
|View full text |Cite
|
Sign up to set email alerts
|

Heart sound cancellation from lung sound recordings using recurrence time statistics and nonlinear prediction

Abstract: Heart sounds (HS) obscure the interpretation of lung sounds (LS). This letter presents a new method to detect and remove this undesired disturbance. The HS detection algorithm is based on a recurrence time statistic that is sensitive to changes in a reconstructed state space. Signal segments that are found to contain HS are removed, and the arising missing parts are replaced with predicted LS using a nonlinear prediction scheme. The prediction operates in the reconstructed state space and uses an iterated inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 11 publications
3
33
0
Order By: Relevance
“…The percentages of total positive k i decreased for high flow lung sounds and stayed approximately the same for low and medium flows. The results of state space analysis of heart sounds using the recurrence statistic reported in [4] complement the finding of our study. The recurrence statistic is related to the distance between state space vectors, and it was found to be lower for regions of lung sound recordings outside of heart sounds [4].…”
Section: Discussionsupporting
confidence: 87%
“…The percentages of total positive k i decreased for high flow lung sounds and stayed approximately the same for low and medium flows. The results of state space analysis of heart sounds using the recurrence statistic reported in [4] complement the finding of our study. The recurrence statistic is related to the distance between state space vectors, and it was found to be lower for regions of lung sound recordings outside of heart sounds [4].…”
Section: Discussionsupporting
confidence: 87%
“…If it is chosen too low, the hypersphere would be low on data, and if r is chosen too high, the hypersphere will contain misleading information from erroneous parts of the reconstructed state space. In this work, r is adaptive, and it becomes lower if there are not lobe detection corresponding to S1 and S2 in Ψ(r) [6].…”
Section: Recurrence Time Statistics (Rts)mentioning
confidence: 99%
“…Another approach to segment PCG is based on time-frequency analysis, implemented with wavelet transform or distributions belonging to the Cohen's quadratic class. That PCG signal exhibits nonlinear dynamics, this fact motivates the use of complexity measures [5], and RTS [6]. In our work, we combine the best of these methodologies with the aim of developing a reliable algorithm capable of segmenting the PCG signal with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…For lung sound analysis, signal processing strategies based on conventional time, frequency, or time-frequency signal representations have been proposed for heart sound cancelation. Representative strategies include entropy calculation (7) and recurrence time statistics (8) for heart sound detection-and-removal followed by lung sound prediction, adaptive filtering (e.g., (9; 10)), time-frequency spectrogram filtering (11), and time-frequency wavelet filtering (e.g., (12)(13)(14)). Subjective assessment, however, has suggested that due to the temporal and spectral overlap between heart and lung sounds, heart sound removal may result in noisy or possibly "non-recognizable" lung sounds (15).…”
Section: Introductionmentioning
confidence: 99%